Implementation of Extreme Programming in the Asoka Makassar Integrated Early Childhood Education E-Book Activities - Neneng Awaliah; Andryanto Aman; Nur Mustika; Erwin Gatot Amiruddin; Made Nuryani (Ceddi Journal of Education, 2022)
Early childhood education is a pre-school education that must be a concern for parents that can continue to be the responsibility of teachers in early childhood education institutions (PAUD), one of the main philosophies in educating early childhood, namely forging, honing, loving and fostering. Foster care means an effort to realize personality and identity so that children have various main characteristics, namely integrity, faith and piety. This research was conducted with the intention of monitoring children's activities while in PAUD Asoka Makassar. This system is in the form of an electronic activity book or commonly called an e-book of activities, in the implementation of an e book of activities in the form of managing school activities and monitoring students. By applying the Extreme programming method (XP), and visual studio code as a code editor. By implementing this system, it can make it easier for schools and parents to monitor children's activities during school and improve the quality of the school.